Factor causing late referral of CKD patients to Nephrology care - Beena Salman; Muhammad Tahir; Ruqaya Qureshi; Murtaza Fakhruddin Dhrolia; Aasim Ahmad; Salman Imtiaz (Archives of Renal Diseases and Management - Peertechz Publications, 2017)
Introduction: Identification of the disease in its early period changes the outcome. Early reorganition of the chronic kidney disease and a timely referral to nephrologist also affects the prognosis of the disease.The factors which contribute in late referral are well known in the western population. There is a need to look into the factors in our population. Methods:This cross sectional study was conducted in the nephrology unit of Dow university hospital and The Kidney center post graduate medical institute. A structured questionnaire was used to collect the data on sociodemographic characteristics. The stages of CKD were determined by the creatinine clearance or glomerular filtration rate at the time of first presentation at hospital. To measure association of stage of CKD with categorical study variables, chi-square test was executed. Level of significance was considered at 5%. Results: Among the different stages of CKD, most of the patients (31.2%) first time presented in the hospital with stage V kidney disease; on the other hand only 8.7% of total patients came in stage 1. Gender, age,  socioeconomic  status  and  education  were  associated  with  late  referral  of  the  CKD  patients  in  the hospital (p value≤ 0.05) while rural and urban residence was not associated with referral time of patients.